ChemInform Abstract: Synthesis of Functionalized Phenols via the Cascade Reactions of Allenic Ketones with β‐Diketones. Issue 49 (December 2015) - Fan, Xuesen; Yan, Meng; He, Yan; Shen, Nana; Zhang, Xinying
Abstract: A broad spectrum of highly substituted phenols/2‐hydroxyalkyl ketones is readily available in a selective manner in the presence of K2 CO3 in different solvents.